The Taking Charge After Stroke (TaCAS) study protocol: a multicentre, investigator-blinded, randomised controlled trial comparing the effect of a single Take Charge session, two Take Charge sessions and control intervention on health-related quality of life 12 months after stroke for non-Māori, non-Pacific adult New Zealanders discharged to community living - Mark Weatherall; Harry McNaughton; Vivian Wai Yin Fu (BMJ Open)
Introduction Stroke is one of the leading causes of disability worldwide. Recent data support the possibility that person-centred, self-management interventions can reduce dependence after stroke. However, there is limited information on the generalisability and optimum dose of these interventions.Methods The Taking Charge After Stroke (TaCAS) study is a multicentre, investigator-blinded, randomised controlled trial recruiting 400 participants following acute stroke from seven hospitals in New Zealand. All patients discharged to community living who have ongoing symptoms at time of discharge (modified Rankin scale>0) will be eligible. Participants will be randomly assigned to one Take Charge session, two Take Charge sessions 6 weeks apart or control.Outcomes The primary outcome will be the Physical Component Summary score of the Short-Form 36 at 12 months post stroke. Secondary outcomes will include dependence (modified Rankin scale), performance in activities of daily living (Barthel Index) and carer strain (Caregiver Strain Index), at 6 and 12 months post stroke. All analyses will be conducted on an intention-to-treat basis.Ethics and dissemination The TaCAS study is funded by a Health Research Council of New Zealand grant. It has been approved by the Central Health and Disability Ethics Committee (15/CEN/115). Results will be published and presented at relevant stroke meetings within New Zealand and internationally, informing the use of a self-management intervention after stroke.Trial registration Australia and New Zealand Clinical Trials Registry ACTRN12615001163594. Date registered 02-11-2015. Medical Research Institute of New Zealand Registry TCS01. Universal trial number U1111-1171-4127.